Study on student peer assessment for practical task evaluation in thermodynamics course - Ibrahim, Mastura Binti; Muhamad, Zalinawati Binti; Wahid, Siti Aishah Binti (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2021)
Peer assessment is a process whereby students peers grade assignment or practical task based on a lecturer’s guidelines. A set of Rubrics are often used in conjunction with peer assessment. The objective of study is to design an instruments for student peer assessment in practical task evaluation for Thermodynamics laboratory. The data were collected from 37 respondents in Thermodynamics laboratory through a set of questionnaires. The data were analyzed in descriptive manner of score mean and standard deviation by using Microsoft Excel 2013. The findings show a positive reaction from the respondents over the implementation of peer assessment. The score mean is 3.58. Implementation of Peer assessment in Thermodynamics course to support not only students' learning but also improve their understanding of the assessment processes themselves.